`x^2 + 4xy - y^3 = 6` Find `dy/dx` by implicit differentiation.

Textbook Question

Chapter 2, Review - Problem 78 - Calculus of a Single Variable (10th Edition, Ron Larson).
See all solutions for this textbook.

1 Answer | Add Yours

hkj1385's profile pic

hkj1385 | (Level 1) Assistant Educator

Posted on

`(x^2) + 4xy - (y^3) = 6`

differentiating

`2x + 4y + 4x(dy/dx) - 3(y^2)*(dy/dx) = 0`

`or, 2(x+2y) = (dy/dx)*[3(y^2) - 4x]`

`or, dy/dx = [2(x+2y)]/[3(y^2)-4x]`

``

We’ve answered 318,919 questions. We can answer yours, too.

Ask a question